THE CORRELATION OF READING HABIT ON STUDENTS’ ENGLISH LEARNING ACHIEVEMENT AT ECONOMIC COLLEGE OF RIAU - Bishry, Hasanul (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The purpose in this study clearly investigate the correlation of reading habit on students’ English learning achievement at economic college of Riau. It was motivated that students in this college were lack of motivation and interest to study English. In additional, students’ habit in reading should be give attention. This study used quantitative research as method. The population in this study was 5th semester students at economic college of Riau in academic year 2022/2023. The sample was 74 students and it took by using slovin formula. In spreading the questionnaire used random sampling. The finding in this study showed that students’ reading habit was in moderate category. Meanwhile, students’ English learning achievement was in good category. The correlation between variables showed that there was significant correlation between reading habit and students’ English learning Achievement at Economic College of Riau. The correlation was in Strong Correlation.